Program Pemberdayaan Umat (Prodomart) Mahasiswa Program Studi (Prodi) Magister Kesehatan Masyarakat Universitas Ahmad Dahlan (UAD)Yogyakarta Melalui Webinar dengan Tema Beban Kerja dan Kesehatan Mental - Puguh Prasetya; Dian Riskha Amalia Nurlette; Atni Setiyo Ningsih (Politeknik Piksi Ganesha Indonesia, 2023)
The greater the demands on employees, the greater the workload. High-intensity workloads can cause health problems and decrease productivity levels in workers' self-confidence, changes in behavior and work stress. Webinar with the theme Workload and Mental Health. This community empowerment program also aims to increase the knowledge of workload webinar participants and the knowledge of webinar participants about mental health. This empowerment method uses online webinar techniques and questionnaires in the form of pre-tests and post-tests for knowledge level. The community empowerment population is all workers who can take part in the online webinar with a total of 78 participants. The results obtained after the community empowerment activities, after the Paired Sample T-Test was carried out, there was an increase in participants' knowledge about workload and mental health by 40.2 with a significance value of <0.05. Conclusion: Webinar activities increase participants' knowledge about workload and mental health.